2010
DOI: 10.1152/ajpheart.00909.2009
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cardiac output alters the mechanisms of the muscle metaboreflex pressor response

Abstract: Muscle metaboreflex activation during submaximal dynamic exercise in normal subjects elicits a pressor response primarily due to increased cardiac output (CO). However, when the ability to increase CO is limited, such as in heart failure or during maximal exercise, the muscle metaboreflex-induced increases in arterial pressure occur via peripheral vasoconstriction. How the mechanisms of this pressor response are altered is unknown. We tested the hypothesis that this change in metaboreflex function is dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 40 publications
3
49
0
1
Order By: Relevance
“…These substances can trigger cardiovascular reflexes (i.e., the so called "metaboreflex"), thereby activating the sympathetic nervous system, which in turn increases blood pressure to guarantee sufficient metabolite wash-out from the contracting muscle (19,39). In normal individuals, this task is accomplished with a complex hemodynamic response that encompasses complex interplay between myocardial performance, cardiac preload, afterload, and HR (3,6,9,13,14,24,33,40,51,56). Recent evidence suggests that, at least in healthy subjects, when the metaboreflex is activated by PEMI, a central role in the described metaboreflex-induced blood pressure response is played by the possibility to keep constant or to increase SV, thereby maintaining or increasing CO, since HR is not usually involved in the phenomenon (3, 9 -11, 25, 38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These substances can trigger cardiovascular reflexes (i.e., the so called "metaboreflex"), thereby activating the sympathetic nervous system, which in turn increases blood pressure to guarantee sufficient metabolite wash-out from the contracting muscle (19,39). In normal individuals, this task is accomplished with a complex hemodynamic response that encompasses complex interplay between myocardial performance, cardiac preload, afterload, and HR (3,6,9,13,14,24,33,40,51,56). Recent evidence suggests that, at least in healthy subjects, when the metaboreflex is activated by PEMI, a central role in the described metaboreflex-induced blood pressure response is played by the possibility to keep constant or to increase SV, thereby maintaining or increasing CO, since HR is not usually involved in the phenomenon (3, 9 -11, 25, 38).…”
Section: Discussionmentioning
confidence: 99%
“…MEAN BLOOD PRESSURE RESPONSE (MBP) to metaboreflex activation in healthy individuals is normally the consequence of increases in both systemic vascular resistance (SVR) and cardiac output (CO) (3,9,10,12,14,24,29,31,54,56). This response is achieved as the result of an elevation in sympathetic tone, which produces arteriolar constriction and enhancement in myocardial performance and in cardiac preload (18,35,39).…”
Section: The Main New Finding Of the Present Investigation Is That Obmentioning
confidence: 99%
“…Although differences in the type of exercise and muscle mass used in the exercise could potentially affect the results, an alternative explanation for this inconsistency is that the components of the muscle metaboreflex-mediated pressor response vary widely among human subjects. Previous studies (25,26,30,67) have shown that activation of the muscle metaboreflex during submaximal treadmill exercise in dogs with reduced hindlimb blood flow elicits a pressor response mediated primarily by an increase in CO. However, the mechanism of the pressor response shifts to increased peripheral vasoconstriction when the ability to increase CO is limited, such as in heart failure or during maximal exercise (2,20).…”
mentioning
confidence: 99%
“…However, the mechanism of the pressor response shifts to increased peripheral vasoconstriction when the ability to increase CO is limited, such as in heart failure or during maximal exercise (2,20). In addition, that shift has also been observed when the normal rise in CO is either pharmacologically or mechanically removed (26,54). Based on these findings, it is conceivable that individuals with a small or no increase in CO during PEMI, and maybe even during isometric exercise, may show substantial peripheral vasoconstriction.…”
mentioning
confidence: 99%
“…All animals were accustomed to human handling before they were surgically instrumented in two different procedures (sternotomy and left flank abdominal surgery), as described in several previous studies (10,11,14). Briefly, using aseptic procedures, a midline sternotomy was performed, and a fully implantable telemetered blood pressure transducer (model no.…”
Section: Methodsmentioning
confidence: 99%